Coal to graphene-based materials: Evaluating coal as a potential feedstock to pave way for large scale production of graphene and related materials, a review - Boitshepho Ivy Marakalala; Victor K. Manisa; Tumeletso Lekgoba; Freeman Ntuli; Vepika Kandjou (Next Materials)
Of recent, coal and other abundant carbon-rich materials are emerging as potential feedstocks and precursors in the production of graphene-based materials such as pristine graphene and graphene oxide and reduced graphene oxide. Considering the abundance of coal reserves globally, using coal as a feedstock in the production of graphene-based materials offers potential in large scale production and paving a way towards the realisation of industrial application of these versatile nanomaterials. The paper explores the prospective of coal as a raw material for graphene and graphene oxide production, by evaluating the quality of the graphene and graphene oxide produced in terms of the aspect ratio, singularity of the sheets and the general physicochemical characteristics. The novelty of the production of graphene-based material from coal means that limited works exist in this area hence the significance of this review. The review is also geared towards valorising various coal type feedstocks including stock piling coal fines in various regions especially in Sub-Saharan Africa. An overview of possible applications of the resultant coal-based graphene and graphene oxide are reviewed.